The Impact of Gestational Diabetes on Long-Term Cognitive Function: A Prospective Cohort Study with Neuroimaging Correlates in Bandung, Indonesia - Miranda Aisah; Lestini Wulansari; Vania Delma; Reza Andrianto; Zahra Amir; Dedi Sucipto; Agnes Mariska; Saurie Hernandez (Sriwijaya Journal of Neurology, 2024)
Introduction: Gestational diabetes mellitus (GDM) is a growing public health concern with potential long-term consequences for both mother and child. Emerging evidence suggests that GDM may impact maternal cognitive function, but the underlying mechanisms remain unclear. This prospective cohort study investigates the association between GDM and long-term cognitive function in mothers, exploring potential neuroimaging correlates. Methods: Pregnant women were recruited from antenatal clinics in Bandung, Indonesia, between 2018 and 2020. GDM was diagnosed using the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria. Cognitive function was assessed at 6 months, 1 year, and 3 years postpartum using a comprehensive neuropsychological battery. A subset of participants underwent structural and functional magnetic resonance imaging (MRI) at 3 years postpartum. Results: Women with GDM exhibited lower scores on tests of executive function, processing speed, and memory compared to women without GDM at all follow-up assessments. MRI analysis revealed alterations in brain structure and function inwomen with a history of GDM, including reduced gray matter volume in the prefrontal cortex and hippocampus, and altered functional connectivity within the default mode network. Conclusion: GDM is associated with long-term cognitive impairment in mothers, possibly mediated by structural and functional brain changes. These findings highlight the importance of early identification and management of GDM to mitigate potential long-term cognitive consequences.